AN EXTENSIVE SOLUTION TO PREVENT WAX DEPOSITION FORMATION IN GAS-LIFT WELLS - Nguyen Van, Thang; Nikolaevich Aleksandrov, Aleksandr; Konstantinovich Rogachev, Mikhail (Journal of Applied Engineering Science, 2022)
In recent years, an insurmountable problem in high-wax oil production has been the intensive formation of organic deposits in the bottom-hole zone of the formation, downhole and surface equipment, leading to a dramatic loss in wells production, transportation capability, and subsequently has a detrimental effect on efficiency. Gas-lift is a widely used method, where compressed high-pressure gas is injected through the tubing annulus. Consequently, the current fluid level in the annulus decreases and increases in the tubing string. The compressed gas enters the tubing through gas-lift valves, mixing with the liquid. During production, changes in pressure, temperature, and fluid composition along the well bore highly depend upon the compressed gas injected into the well.  At temperatures below the wax appearance temperature, organic wax crystals will form either in bulk volumes of fluid or on cold surfaces of equipment, consequently, covering the surface. Wax formation is a hazardous and costly task in the oil and gas industry, especially when operating gas-lift wells. Hence, the prevention of wax formation in gas-lift wells is of utmost importance. Although, numerous methods have been implemented to handle the wax formation problem in recent decades, questions concerning their economic viability as well as their effectiveness remain relevant.In this paper, a complete algorithm for determining changes in the oil component composition in a gas-lift well during the injection of associated petroleum gas is detailed. The obtained results play a pivotal role in the study of wax deposition. A technological scheme has been developed to prevent wax deposit formation in the tubing strings during gas-lift well operation. A simulation using the introduced process and technology has been run, and an observed result obtained. After running the simulation, we determined the optimal composition of the associated petroleum injection gas based on the required flow rate of the working agent and the lowest value of the wax appearance temperature. This method offers potential solutions to increasing gas-lift well production efficiency under complex wax formation conditions.
Keywords: high-wax oil; operation of gas-lift wells; wax appearance temperature; optimal composition; associated petroleum gas